2009
DOI: 10.1016/j.chom.2008.12.004
|View full text |Cite|
|
Sign up to set email alerts
|

Recombinant Viral Vaccines Expressing Merozoite Surface Protein-1 Induce Antibody- and T Cell-Mediated Multistage Protection against Malaria

Abstract: SummaryProtecting against both liver and blood stages of infection is a long-sought goal of malaria vaccine design. Recently, we described the use of replication-defective viral vaccine vectors expressing the malaria antigen merozoite surface protein-1 (MSP-1) as an antimalarial vaccine strategy that elicits potent and protective antibody responses against blood-stage parasites. Here, we show that vaccine-induced MSP-1-specific CD4+ T cells provide essential help for protective B cell responses, and CD8+ T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
101
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 32 publications
9
101
0
1
Order By: Relevance
“…However, the data clearly establish that strong and detectable IFN-g T cell responses can be primed and boosted by immunization against both component alleles, and this was independently observed in two clinical trials of the same vaccines. The observation of strong cellular responses against the MSP1 33 region (in comparison with MSP1 19 ) is in good agreement with many previous studies that have assessed T cell recognition within MSP1 42 in both animal models (20,45) and humans (46)(47)(48)(49). Note also that future studies could further assess such phenomena in the context of other T cell phenotype readouts, including different cytokine production.…”
Section: Figure 7 (A) Ifn-g Cd8supporting
confidence: 79%
See 2 more Smart Citations
“…However, the data clearly establish that strong and detectable IFN-g T cell responses can be primed and boosted by immunization against both component alleles, and this was independently observed in two clinical trials of the same vaccines. The observation of strong cellular responses against the MSP1 33 region (in comparison with MSP1 19 ) is in good agreement with many previous studies that have assessed T cell recognition within MSP1 42 in both animal models (20,45) and humans (46)(47)(48)(49). Note also that future studies could further assess such phenomena in the context of other T cell phenotype readouts, including different cytokine production.…”
Section: Figure 7 (A) Ifn-g Cd8supporting
confidence: 79%
“…CD8 + T cells have been shown to be protective in the Plasmodium yoelii mouse model at both the liver stage (19,20) and blood stage of malaria infection (21). CD8 + T cells specific for blood-stage Ags potentially target merozoite-derived Ags during the late stages of preerythrocytic parasite development within infected hepatocytes (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such particle presentation could be achieved by using either recombinantly expressed antigen on whole-killed bacteria or viruses. For example, mouse studies using recombinant adenovirus encoding MSP-1 demonstrated "protection" (defined by the authors as delayed and lower parasitemia) (Draper et al, 2009).…”
Section: Future Directionmentioning
confidence: 99%
“…23 For example, P. yoelii MSP-1 33 induces effector T cells that could assist in protective B cells response and mediate significant antiparasitic activity against P. yoelii. 24,25 Plasmodium falciparum MSP-1 33 is naturally immunogenic because antibodies against this antigen could be detected in serum of P. falciparum-exposed blood donors. 26 It was further shown that that T cell response and antibodies against MSP1 were induced in human clinical trials by using P. falciparum MSP-1, in which epitopes responsible for cytokine production and memory response development were localized to the 33-kDa region of MSP-1 42 .…”
Section: Introductionmentioning
confidence: 99%